Chromosome Abnormalities and Gene Rearrangements in Malignant Lymphoma - Maseki, Nobuo; Kaneko, Yasuhiko; Sakurai, Masaharu (Journal of the Japan Society of the Reticuloendothelial System, 1989)
The incidences of chromosome abnormalities involving the bands including the loci of the immunoglobulin genes and the T cell receptor genes were studied in 54B lymphomas and 44T lymphomas. Breaks in band 14q32, the site of the immunoglobulin heavy chain genes, were more frequent in B lymphoma (37%) than in T lymphoma (16%) (p<0.05). Breaks in band 14q11, where the T cell receptor alpha chain gene resides, were found in only T lymphoma (p<0.05). All the other bands, i.e. 2p12, 7p15, 7q35, 11q23, and 22q11, where immunoglobulin light chain genes, T cell receptor beta and gamma chain genes, and T3-complex genes reside, however, were involved much less frequently. We conclude that chromosome aberrations may be detectable on light microscopy only in part of the cases which undergo molecular rearrangements of immunoglobulin or T cell receptor genes in malignant lymphoma.